Implementasi Kebijakan Penguatan Moderasi Beragama (PMB) dalam Kurikulum Pada Perguruan Tinggi Keagamaan: (Studi Kasus Pada IAIN, IAKN dan IAHN Tampung Penyang Palangka Raya) - Ajahari Ajahari; Puspita Puspita; Teddy Teddy; Nahdiyatul Husna; Yosal Iriantara (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
The Policy on Strengthening Religious Moderation is a national policy and within the scope of the Ministry of Religion it is a strategic, priority and serious policy to implement. This study uses a descriptive qualitative approach which seeks to present information, data in the form of descriptions based on data and facts found in the field. The research method is a case study with a purposive sampling technique. The subjects in this study were IAIN, IAKN and IHAN TP Palangka Raya. The results of the study show that there are differences in the implementation of the policy of strengthening religious moderation at the curriculum level in 3 religious universities in Palangka Raya City. Some of the factors constraining the not yet optimal implementation of religious moderation in the curriculum and learning structure are: 1. Internal regulations and organizational structures in the form of SOPs and implementation guidelines that do not yet exist; 2. Limited human and financial resources; 3. Communication relations between organizations that are not yet optimal; 3. Disposition of the implementer, namely the understanding of the implementer that is still uneven; 4. Limited communication